Effect of Tasar Silk Waste on the Mechanical Properties of Jute/Grewia Optiva Fibers Reinforced Epoxy Laminates. Issue 15 (23rd November 2022) - Ranakoti, Lalit; Rakesh, Pawan Kumar; Gangil, Brijesh
ABSTRACT: Waste collected from the agricultural sector can be used as reinforcement in the composites to lower the material cost and encourage the renewable material to reduce carbon footprints. Hence, the current investigation evaluates the physical, mechanical, and wear properties of hybrid composite laminates comprising Tasar silk waste (a waste obtained from textile industries), Jute fibers, Grewia optiva (Bhimal tree) and epoxy resin. For this, epoxy reinforced Jute/Grewia optiva fibers laminates were fabricated with varying percentages of Tasar silk waste (TSW) (0, 4, 6, 8, 10, 12, and 14 wt.%). Experimental results reveal that the void fraction increases from 1.8% to 3.4%; an increase in the water absorption took place at all percentages of TSW and become saturated after 216 hours of immersion. The tensile strength increased from 54.44 MPa to 79.16 MPa, and flexural strength increased from 21.91 MPa to 51.22 MPa with 14 wt.% of TSW. Vickers hardness and impact strength was maximum at 12 wt.% of TSW loading. Specific wear rate was observed as inversely proportional to sliding velocity, and directly proportional to normal load. Statistical analysis of the specimens was carried out using the ANOVA technique, which confirms a significant difference between the obtained results.